EFEKTIVITAS METODE PEMBIASAAN MEMBACA ASMAUL HUSNA DALAM MENANAMKAN NILAI AGAMA DAN MORAL PADA ANAK DI RA HASAN MUNADI BANGGLE GUNUNGGANGSIR BEJI PASURUAN - Nanang Rokman Saleh; Muhammad Syaikhon; Machmudah (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
Along with the development and progress of the times marked by the rapid development of information and communication technology called the digital era, in addition to bringing positive value to enrich the nutritional intake of knowledge, It also creates negative values ?in all areas of life, including education, which causes the problem of low religious and moral values ?for students from childhood to adolescence and even adults. Therefore, the most important thing to do is to make efforts to form religious and moral human beings through the cultivation of religious and moral values ?at all levels of education. Raudhatul Athfal (RA) Muslimat Hasan Munadi is one of the educational institutions under the auspices of the Ministry of Religion that applies the habituation method in learning. This study aims to analyze the effectiveness of the Asmaul Husna reading habituation method in instilling religious and moral values? in children at RA Hasan Munadi Banggle Gunung Gangsir Beji Pasuruan. The data sources in this study consisted of primary sources in the form of school principal data, while secondary data in the form of results from observations, interviews, and documentation. Data collection techniques through observation, interviews, and documentation methods. The data analysis technique used the Miles and Huberman analysis method so that it could be seen the effectiveness of the Asmaul Husna reading habituation method in instilling religious and moral values in children at RA Hasan Munadi. The results showed that the method of habituation to read Asmaul Husna in instilling religious and moral values in children at RA Hasan Munadi was very effective